Zygomatic osteotomy for improving aesthetic results in orthognathic surgery: a report of two cases - Demétrio, Maurício Silva; Barbosa, Saulo de Matos; Lima, Raphaela Kassia; Medeiros, Yuri de Lima; Marliére, Daniel Amaral Alves; Assis, Neuza Maria Souza Picorelli (Journal of the Korean Association of Oral and Maxillofacial Surgeons, 2025)
Patients with anteroposterior maxillary deficiency and mandibular prognathism associated with a long-face pattern exhibit reduced anterior and lateral projection of the zygomaticomaxillary complex. Several techniques have been combined with orthognathic surgery to enhance the volume and definition of this region, such as zygomatic osteotomy. Two female patients, aged 22 (Case A) and 29 (Case B), with class II (Case A) and III (Case B) malocclusion, respectively, complained about facial aesthetics due to a long face and lack of malar projection. Le Fort I osteotomy to advance the maxilla, bilateral mandibular ramus osteotomy to set back the mandible, mentoplasty for advancement and width reduction, and zygomatic osteotomy were erformed. The patients underwent computed tomography scans, and superimposed images indicated that a volumetric increase in the malar region was achieved through the anterolateral movement of the zygomatic body. Improvements were noted in the paranasal region (Case A), better alignment of the upper and lower lips, the chin region, and an improved chin-neckline ratio (in both cases). The patients were satisfied with the results and are under follow-up. In summary, zygomatic osteotomy combined with orthognathic surgery proved to be a predictable and safe strategy for increasing malar prominence, with satisfactory aesthetic and functional outcomes.